PENINGKATAN LITERASI KESEHATAN KELUARGA MELALUI EDUKASI ISLAMI TENTANG DETEKSI DINI DAN PENCEGAHAN KOMPLIKASI DIABETES MELLITUS DI GAMPONG TEUNGOH, KECAMATAN NISAM, KABUPATEN ACEH UTARA - Diauddin, Diauddin; Said Taufiq; Muzakkir; Fitriani Agustina; M. Jamil Fauzi (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2026)
Diabetes Mellitus (DM) is a non-communicable disease with an increasing prevalence that significantly impacts the quality of life of families. Low family health literacy, particularly regarding early detection and prevention of DM complications, is a major problem in the community. This Community Service activity aims to improve family health literacy through Islamic-based education in the community of Gampong Teungoh, Nisam District, North Aceh Regency. The methods used are an educational-participatory approach through Islamic thematic lectures, interactive discussions, early detection skills training, and simple blood sugar screening. The results of the activity showed an increase in the knowledge, skills, and awareness of participants—especially housewives—in recognizing risk factors, early symptoms, and efforts to prevent DM complications. Education based on Islamic values proved to increase participation and acceptance of the program. This activity concluded that the integration of health education with religious values and the use of places of worship is effective as a promotive and preventive strategy for DM at the community level